(untitled) (Quinto Sol, 2013)
The study of diverse documentary sources originating from the Argentine national state suggests that the early efforts to effectively incorporate to the nation the new territories of the Pampa and Patagonia conquered in the second half of decade of 1870 were unsuccessful. We propose to support this hypothesis, in the North Patagonia case, through the analysis of National Congress minutes, presidential messages, memories of the Department of Interior and War and memories of the first governors of the National Territories of Patagonia, Río Negro and Neuquén.